Southern green criminology : a science to end ecological discrimination - Goyes, David Rodríguez (Perspectives on crime, law and justice in the Global South, 2019)
The pressing nature of environmental threats, such as: climate change, land-grabbing, biopiracy, animal exploitation and human environmental victimisation, are pushing the entire world to seek alternatives to prevent environmental damage in every corner of the globe. Southern Green Criminology focuses on the threat the western world poses to the rest of the globe, and how Western imposed ideas of progress are damaging the planet, especially the southern hemisphere.In the past five years, the attention of green criminologists has been directed at the Global South as the geographical site that experiences the severest consequences of harmful environmental practices. Such criminological direction is aimed at combating the environmental harms that affect the geographical and the metaphorical Souths. The main topic of this book is the conflicts that arise in the interaction between human beings and our natural environment, seen from a Southern perspective with a focus on the victimisation of the South. This book is simultaneously a scientific and a political endeavour, and will prove invaluable to students, researchers and environmental enthusiasts alike.